Acute Kidney Injury in Pediatric Severe Sepsis: An Independent Risk Factor for Death and New Disability. Issue 12 (December 2016) - Fitzgerald, Julie C.; Basu, Rajit K.; Akcan-Arikan, Ayse; Izquierdo, Ledys M.; Piñeres Olave, Byron E.; Hassinger, Amanda B.; Szczepanska, Maria; Deep, Akash; Williams, Duane; Sapru, Anil; Roy, Jason A.; Nadkarni, Vinay M.; et al.
Abstract : Objectives: The prevalence of septic acute kidney injury and impact on functional status of PICU survivors are unknown. We used data from an international prospective severe sepsis study to elucidate functional outcomes of children suffering septic acute kidney injury. Design: Secondary analysis of patients in the Sepsis PRevalence, OUtcomes, and Therapies point prevalence study: acute kidney injury was defined on the study day using Kidney Disease Improving Global Outcomes definitions. Patients with no acute kidney injury or stage 1 acute kidney injury ("no/mild acute kidney injury") were compared with those with stage 2 or 3 acute kidney injury ("severe acute kidney injury"). The primary outcome was a composite of death or new moderate disability at discharge defined as a Pediatric Overall Performance Category score of 3 or higher and increased by 1 from baseline. Setting: One hundred twenty-eight PICUs in 26 countries. Patients: Children with severe sepsis in the Sepsis PRevalence, OUtcomes, and Therapies study. Interventions: None. Measurements and Main Results: One hundred two (21%) of 493 patients had severe acute kidney injury. More than twice as many patients with severe acute kidney injury died or developed new moderate disability compared with those with no/mild acute kidney injury (64% vs 30%; p < 0.001). Severe acute kidney injury was independently associated with death or new moderate disability (adjusted odds ratio, 2.5; 95% CI, 1.5–4.2; p = 0.001) after adjustment for age, region, baseline disability, malignancy, invasive mechanical ventilation, albumin administration, and the pediatric logistic organ dysfunction score. Conclusions: In a multinational cohort of critically ill children with severe sepsis and high mortality rates, septic acute kidney injury is independently associated with further increased death or new disability. Abstract : Supplemental Digital Content is available in the text.